Prognostic value of dipyridamole stress perfusion cardiovascular magnetic resonance in elderly patients >75 years with suspected coronary artery disease. (5th August 2020) - Pezel, Théo; Sanguineti, Francesca; Kinnel, Marine; Hovasse, Thomas; Garot, Philippe; Unterseeh, Thierry; Champagne, Stéphane; Louvard, Yves; Morice, Marie Claude; Garot, Jérôme
Abstract: Aims : There are only very few data on the prognostic value of stress cardiovascular magnetic resonance (CMR) in elderly people, while life expectancy of the general population is steadily increasing. Therefore, this study aims to assess the prognostic value of vasodilator stress perfusion CMR in elderly >75 years. Methods and results : Between 2008 and 2017, we included consecutive elderly >75 years without known coronary artery disease (CAD) referred for dipyridamole stress CMR. They were followed for the occurrence of major adverse cardiovascular events (MACE) including cardiac death or non-fatal myocardial infarction. Univariate and multivariate analyses were performed to determine the prognostic value of ischaemia or late gadolinium enhancement. Of 754 elderly individuals (82.0 ± 3.9 years, 48.4% men), 659 (87.4%) completed the follow-up with median follow-up of 4.7 years. Using Kaplan–Meier analysis, the presence of myocardial ischaemia was associated with the occurrence of MACE [hazard ratio (HR) 5.38, 95% confidence interval (CI): 3.56–9.56; P  < 0.001]. In a multivariable Cox regression including clinical characteristics and CMR indexes, inducible ischaemia was an independent predictor of a higher incidence of MACE (HR 4.44, 95% CI: 2.51–7.86; P  < 0.001). In patients without ischaemia, the occurrence of MACE was lower in women when compared with men ( P  < 0.01). Conclusion : Stress CMR is safe and has discriminative prognostic value in elderly, with a significantly lower event rate of future cardiovascular event or death in subjects without ischaemia or infarction.